Development and distortion of Malaysian public-private partnerships - patronage, privatised profits and pitfalls - Beh, Loo See (Blackwell Publishing, 2010)
This article examines the politicisation of systemic patronage and privatised profits in the development of Public-Private Partnerships (PPPs) in Malaysia. Issues associated with inadequate regulatory frameworks, control, accountability and poorly managed risks, demonstrate that much more effective reforms are required to reduce further pitfalls, to protect public interests and to uphold the integrity of the public service and government. The adoption of a transparent procurement and evaluation system will be a challenging task if public and investor confidence is to be built up and strategic partnerships in the complex web of governance and administrative relationships in the governance of PPPs are to be developed effectively. Finally directions of reform and lessons learnt are suggested.